A Narrative Inquiry of a Non-native EFL Teacher’s Reflection on Reading and Writing Proficiency - Lenni Novrianti Purba; Sri Sumarni (Indonesian Journal of Foreign Language Studies, 2026)
Self-reflection implies a critical approach to evaluating one’s thoughts and acts of achieving something. This study aimed to explore the experiences of acquiring the English language throughout the years as a non-native EFL teacher focusing on reading and writing skills. This study employed a narrative inquiry design to report the experiences and reflections on how the EFL teacher has developed her reading and writing proficiency. The data were collected and analyzed by employing narrative analysis. The study showed how the authentic materials used by the EFL teacher during her learning and teaching experiences played a significant role. In addition, the study indicates the importance of reflecting on one’s experience in acquiring English as a foreign language to plan the proper techniques to be implemented in the class..